Fetal and neonatal effects of anticoagulants used in pregnancy: a review - Yurdakök, Murat (The Turkish Journal of Pediatrics, 2012)
There are several relative (promising regarding a reduction in placenta-mediated complications such as preeclampsia) and absolute (e.g. a recurrent or recent thromboembolic event, mechanical heart valves) reasons for use of anticoagulant drugs during pregnancy. Warfarin readily crosses the placenta because of its low molecular weight, and is associated with a distinctive embryopathy known as fetal warfarin syndrome when exposure occurs between the sixth and twelfth weeks of gestation. Warfarin embryopathy may be avoided by stopping warfarin and switching to heparin when pregnancy is achieved or as soon as possible after conception. Heparins, unfractionated heparin and low molecular weight heparin are the preferred agents for anticoagulation in pregnancy because they show no transplacental passage due to their high molecular weights. Both heparins and warfarin are safe for the infant during breastfeeding. Aspirin is prescribed with increasing frequency to reduce the risk of miscarriage and poor pregnancy outcome. Although aspirin crosses the placenta, it is safe in low doses. However, the safety of higher doses of aspirin during the first pregnancy is uncertain.